De novo FZR1 loss-of-function variants cause developmental and epileptic encephalopathies - TÜRKDOĞAN, DİLŞAD (My University, 2021)
FZR1, which encodes the Cdh1 subunit of the Anaphase Promoting Complex, plays an important role in neurodevelopment by regulating the cell cycle and by its multiple post-mitotic functions in neurons. In this study, evaluation of 250 unrelated patients with developmental and epileptic encephalopathies and a connection on GeneMatcher led to the identification of three de novo missense variants in FZR1. Whole-exome sequencing in 39 patient-parent trios and subsequent targeted sequencing in an additional cohort of 211 patients was performed to identify novel genes involved in developmental and epileptic encephalopathy. Functional studies in Drosophila were performed using three different mutant alleles of the Drosophila homolog of FZR1 fzr. All three individuals carrying de novo variants in FZR1 had childhood onset generalized epilepsy, intellectual disability, mild ataxia and normal head circumference. Two individuals were diagnosed with the developmental and epileptic encephalopathy subtype Myoclonic Atonic Epilepsy. We provide genetic-association testing using two independent statistical tests to support FZR1 association with developmental epileptic encephalopathies. Further, we provide functional evidence that the missense variants are loss-of-function alleles using Drosophila neurodevelopment assays. Using three fly mutant alleles of the Drosophila homolog fzr and overexpression studies, we show that patient variants can affect proper neurodevelopment. With the recent report of a patient with neonatal-onset with microcephaly who also carries a de novo FZR1 missense variant, our study consolidates the relationship between FZR1 and developmental epileptic encephalopathy, and expands the associated phenotype. We conclude that heterozygous loss-of-function of FZR1 leads to developmental epileptic encephalopathies associated with a spectrum of neonatal to childhood onset seizure types, developmental delay and mild ataxia. Microcephaly can be present but is not an essential feature of FZR1-encephalopathy. In summary, our approach of targeted sequencing using novel gene candidates and functional testing in Drosophila will help solve undiagnosed myoclonic atonic epilepsy or developmental epileptic encephalopathy cases.
Keywords: developmental epileptic encephalopathy; Drosophila model of neurodevelopmental disorders; functional validation of novel variants; FZR1; myoclonic atonic epilepsy